Analysis of acquired human cytomegalovirus infections by polymerase chain reaction. - Bale, J F (1993)
We used the polymerase chain reaction and primers corresponding to three regions of the human cytomegalovirus (HCMV) genome to study HCMVs isolated from 16 children attending a single day-care center and the father of two children in the same center. When we analyzed isolates with primers for the pp65 and major immediate-early genes, we observed nearly uniform amplification yielding products of predicted sizes. By contrast, primers for the a sequence demonstrated variability among HCMV strains, supporting the use of these primers as an epidemiologic tool. Analysis of a-sequence products from two isolates demonstrated 50 to 70% nucleotide homology with the a sequence of HCMV Towne strain DNA. We observed 95% nucleotide homology for the two a-sequence products derived from the father-child pair. Analysis of day-care center isolates indicated that two children excreted two distinct HCMV strains during the study interval.